Dinamika Referensi Jodoh Ideal dan Terlarang dalam Konstruksi Kekerabatan Masyarakat Moncongkomba Gassing Gau Kabupaten Takalar - Hariandini .; Darman Manda (PREDESTINATION: Journal of Society and Culture, 2023)
Abstract: This study aims to determine the standardization or conditions for ideal and forbidden marriages in Moncongkomba Gassinggau Village. This type of research is descriptive qualitative, in which the researcher emphasizes observation and in-depth interviews in collecting data for the process of the validity of this research, but still uses documentation. After obtaining the intended data or information, the next step taken by the researcher is to systematically describe the information or data and then analyze it using comparison and integration with existing theories. The results of this study indicate that in the Moncongkomba Gassinggau village community there are several things that are very guarded (1) the village community really maintains the lineage that is already there, this is inseparable from the intervention of their extended family in protecting offspring, (2) the marriage process in the village this is something that is very sacred so that all the requirements that exist for the two bride and groom are very obligatory, (3) the village community until now still highly respects and maintains existing customs so that they are not eroded by the era itself because these customs is their basis in society  Keywords: Matchmaking, Kinship, Marriage